Scope of the arbitrage pricing theory - Miljan Leković (Anali Ekonomskog fakulteta u Subotici, 2020)
An important element of the positive portfolio theory which in addition to the Capital Asset Pricing Model (CAPM) provides an important contribution in terms of understanding the relationship between return and risk and pricing of assets in the capital market is the Arbitrage Pricing Theory (APT). This theory has been in focus of the economists for decades and is gaining advantage over the CAPM model in theory; however, not in practical terms. The paper aims to search for an answer to the question whether, after the four decades since the APT model has been introduced, there is a consensus in the financial literature on the validity and feasibility of this model in practice. The method of qualitative economic analysis, which allows us to draw valid conclusions on the researched issue based on studying the relevant literature, was applied in this paper. The general conclusion of the research is that the consensus on the key factors of the systematic risk has not yet been reached among economic theorists, researchers and practitioners, which would have eliminated the main deficiency of the APT model, ensured its validity and improved the applicability in practice. The lack of consensus on the most important systematic risk factors has been identified, thus indicating the limited scope of the APT model, which at the same time represents the main result of the research.